Conformational changes and chiroptical switching of enantiopure bis-helicenic terpyridine upon Zn2+ binding. Issue 35 (7th April 2016) - Isla, Helena; Srebro-Hooper, Monika; Jean, Marion; Vanthuyne, Nicolas; Roisnel, Thierry; Lunkley, Jamie L.; Muller, Gilles; Williams, J. A. Gareth; Autschbach, Jochen; Crassous, Jeanne
Abstract : A new type of chiroptical switch based on a bis-helicenic terpyridine, changing conformation upon Zn binding, has been designed. Abstract : The molecular conformation of a bis-helicenic terpyridine system is strongly modified upon binding to Zn(ii ) ion, a process that is accompanied by large changes in the optical and chiroptical properties. This system affords a new type of helicene-based chiroptical switching.